2004
DOI: 10.1016/j.otohns.2004.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Surgery of Cerebellopontine Angle Epidermoid Cysts: Role of the Widened Retrolabyrinthine Approach Combined with Endoscopy

Abstract: RLA combined with endoscopy should be considered as the standard approach for excision of epidermoid cysts. Extension of this approach into a TLA or transcochlear approach will depend on preoperative difficulties and preoperative hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 19 publications
(96 reference statements)
0
19
0
1
Order By: Relevance
“…These masses are described as pearly tumors because of the shiny, smooth, and waxy characteristics of their dry keratin. They can range in size from a few millimeters to 12 cm . The majority of the masses are dermoid or epidermoid cysts …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These masses are described as pearly tumors because of the shiny, smooth, and waxy characteristics of their dry keratin. They can range in size from a few millimeters to 12 cm . The majority of the masses are dermoid or epidermoid cysts …”
Section: Discussionmentioning
confidence: 99%
“…The most common presentation of a median upper neck mass is one that is painless and slow-growing over the course of many years because of accumulation of cutaneous products. 8 Typically, the mass is soft, mobile, and unattached to overlying skin. These masses are described as pearly tumors because of the shiny, smooth, and waxy characteristics of their dry keratin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,44 In such cases, surgeons have resorted to subtotal resection or a staged operation through 2 different approaches: the use of an endoscope to visualize beyond the restrictive limits of the traditional approach or the use of a combined infra-and supratentorial approach. 15,44,48 Altschuler and colleagues 4 found that patients who required multiple procedures resulting in fixed deficits had an extensive lesion and incomplete initial resection, which they believed to be attributable to a limited initial exposure. They contemplated whether the use of a more extensive approach in a first operation would have resulted in better tumor resection, improved outcome, and reduced recurrence.…”
Section: Giant Tumors and Extent Of Resectionmentioning
confidence: 99%
“…Deficits of CNs V-VII and X tend to be transient and typically resolve over 0.5-1.5 years, but damage to CN VIII with hearing loss often persists. 7,14 Less common complications include CSF leakage (4%-8%), symptomatic hydrocephalus (14%), vestibular or cerebellar dysfunction, and pseudomeningocele (5%). 2,3,14,15,21 conclusions Following CPA EC rupture causing pericystic brainstem edema, our patient experienced resolution of her presenting symptoms following subtotal resection without postoperative neurological deficits or complications.…”
mentioning
confidence: 99%